COVID 19 AS A TRIGGER FOR THE OCCURRENCE OF STROKE IN UNDIAGNOSED TRANSIENT FORAMEN OVALE AND THROMBOPHILIA - Nešković, Dragana (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction: COVID-19 is an infection caused by the new coronavirus (SARS-CoV-2). The disease is manifested by respiratory symptoms and can cause serious complications, including acute ischemic stroke (AIS).          The objective of the paper is to point out the complexity of risk factor interaction for the development of AIS after COVID-19.           Case report: A 28-year-old man developed AIS two and a half months after COVID-19. The examination of the patient, who was already on anticoagulant therapy for high D-dimer levels, revealed a left-sided weakness. Computed tomography (CT) showed a fresh frontal ischemic lesion. Upon recanalization, the neurological deficit resolved completely. Further studies revealed a patent foramen ovale (PFO) and congenital thrombophilia.         Conclusion: Additional research is necessary to clarify the role of certain risk factors in the development of AIS even in mild cases of COVID-19.          Keywords: COVID-19, AIS, thrombophilia
Keywords: COVID-19, AIS, thrombophilia